EU Posts Detailed Critique of US Farm Bill - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
On May 15, 2002, the EU posted a detailed critique of the US farm Bill on its...